2020
DOI: 10.1186/s12909-020-02412-x
|View full text |Cite
|
Sign up to set email alerts
|

Peer assessment of professionalism in undergraduate medical education

Abstract: Background Fostering professional behaviour has become increasingly important in medical education and non-traditional approaches to assessment of professionalism may offer a more holistic representation of students’ professional behaviour development. Emerging evidence suggests peer assessment may offer potential as an alternative method of professionalism assessment. We introduced peer assessment of professionalism in pre-clerkship phases of undergraduate medical education curriculum at our i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 17 publications
(52 reference statements)
1
10
0
Order By: Relevance
“…The success of peer assessment could depend on several factors, including the type of peer assessment, e.g. formative or summative; anonymity; and students' accustom towards doing peer assessments (Curran et al 2020;Lerchenfeldt and Taylor 2020). Conducting a successful peer assessment requires the institution to provide clear introductions and help their students prepare well (Curran et al 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The success of peer assessment could depend on several factors, including the type of peer assessment, e.g. formative or summative; anonymity; and students' accustom towards doing peer assessments (Curran et al 2020;Lerchenfeldt and Taylor 2020). Conducting a successful peer assessment requires the institution to provide clear introductions and help their students prepare well (Curran et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…formative or summative; anonymity; and students' accustom towards doing peer assessments (Curran et al 2020;Lerchenfeldt and Taylor 2020). Conducting a successful peer assessment requires the institution to provide clear introductions and help their students prepare well (Curran et al 2020). To enhance learning outcomes, medical students could consciously increase their participation in certain types of educational student engagement.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been described before and seems related to deficiencies in self-assessment [ 27 , 28 ], with students thinking they are doing better than they truly are. The magnitude of increase could also be limited by a ceiling effect attributed to the adopted scale [ 29 ]. This highlights the importance of high-quality performance evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Curran and his collaborators examined the internal structure of a peer assessment tool regarding professionalism and investigated the overall satisfaction with peer assessment. 14 Their study found mixed feelings about peer assessment and identified a lack of constructive feedback as a limitation. A systematic review was conducted to examine the utilization of small-group peer feedback in student learning and professional development.…”
Section: Professionalism In Small Groupsmentioning
confidence: 98%